The brassinosteroid signal transduction pathway - Wang, Zhi-Yong (2006)
Steroids function as signaling molecules in both animals and plants. While animal steroid hormones are perceived by nuclear receptor family of transcription factors, brassinosteroids (BR) in plants are perceived by a cell surface receptor kinase, BRI1. Recent studies have demonstrated that BR binding to the extracellular domain of BRI1 induces kinase activation and dimerization with another receptor kinase, BAK1. Activated BRI1 or BAK1 then regulate, possibly indirectly, the activities of BIN2 kinase and/or BSU1 phosphatase, which directly regulate the phosphorylation status and nuclear accumulation of two homologous transcription factors, BZR1 and BES1. BZR1 and BES1 directly bind to promoters of BR responsive genes to regulate their expression. The BR signaling pathway has become a paradigm for both receptor kinase signaling in plants and steroid signaling by cell surface receptors in general.